Code verification & validation and competitive swimming analysis - Sivamoorthy Kanagalingam (2018)
In competitive swimming analysis, the complexes in 3D six degree of motion simulations have made the dive phase to be the least analyzed to date. Since the time taken by the swimmer to complete the dive phase bank on the opposing forces offered by the water, optimum dive will help to reduce the time required to complete a lap. The research aims at developing a fluid force model that simulates the forces acting on a 3D swimmer's body during water entry. This study intends to determine the effect of forces acting on the swimmer, in the dive phase, with respect to dive velocity and angle using computational modelling. However, the available computational resources are too limited to accomplish such simulations. The motion solvers associated with standard open source codes have two major setbacks; firstly, the mesh elements in the entire fluid domain should be very fine in order to avoid a jump in mesh size, which increases the computational costs. Secondly, the mesh around the swimmer has to be recomputed for each time-step as the swimmer moves. This results in poor near-wall meshes which impairs the accuracy of the simulation. In this study, the dynamic simulations are done using an overset meshing algorithm (OPErA) in association with OpenFOAM. The overset algorithm fixes the mesh around the swimmer and moves it on a fixed background mesh while interpolating between the meshes. The overset meshing algorithm is validated against the standard OpenFOAM solver and used to simulate the diving phase. Multi-phase dynamic motion simulations are initially done using the 2D plate to have an insight into the dynamic simulations including the various criteria that influence the stability and convergence of such simulations. The observations are utilized to run 3D multiphase motion simulations for different angles of entry. The results of the different dive angles are compared to find the efficient angle of dive. The 3D results are also compared with the experimental data extracted from the trial diving footages provided by Singapore Sports Institute.